Interpersonal communication - Julia T. Wood (Thomson/Wadsworth, 2007)
This best-selling text by a leading voice in the field offers a distinct alternative to existing textbooks for the introductory course in interpersonal communication. This text offers a theoretically unified but pragmatic introduction to the concepts, principles, and skills of interpersonal communication in a multicultural society. INTERPERSONAL COMMUNICATION: EVERYDAY ENCOUNTERS consistently integrates ethics and issues of social diversity into coverage of both discussions and mastery of skills, and it shows how interpersonal communication theory and skills pertain to students' daily encounters with others. INTERPERSONAL COMMUNICATION: EVERYDAY ENCOUNTERS pays unparalleled attention to social diversity and emphasizes theories, research, and skills that are anchored in the field of communication